Taro leaf blight hits Western Samoa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Taro, Colocasia esculenta, is one of the main staple food crops of Pacific Island countries and is the principal crop of Western Samoa but the devastating fungal disease, taro leaf blight (Phytophthora colocasiae), has now hit Western Samoa. The...